ANALISA SPEKTRUM DAN PANJANG KOHERENSI BEBERAPA JENIS LAMPU MENGGUNAKAN SPEKTROSKOP PRISMA DAN INTERFEROMETER MICHELSON - Maria '; Minarni '; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
There are three types of commercial lamps available today which are incandescent lamp (light bulb) , fluorescent lamp or Compact Fluorescent Lamp (CFL), and Light Emitting Diode (LED). The three types of lamps can be distinguished by some aspects such as their efficiency, color spectrum, and coherence. This research aimed to obtain and differentiate the color spectrum and coherence of the three kind of lamps. The spectrums were obtained using a prism spectroscope while the coherence levels were analyzed using a Pasco Michelson interferometer. The samples were the three types of lamps with the same power of 5 Watt and CFL lamps with three different power of 5 Watt, 26 Watt, and 45 Watt. The spectrum and fringe pattern of the lamps were captured using a CCD camera and processed by imageJ software. The research results showed that the color spectrum of light bulb and LED produced a continuous spectrum. While the light of light bulb was dominant at red color and LED light at blue color. CFL light spectrums were partly continuous and dominant also in blue color. The different power of CLF produced different brightness, however the spectrum was still dominant in blue. Coherence of the three type of lamps was different as shown in the fringe pattern obtained. CFL produced fringe pattern with high visibility which showed higher coherence than that of LED and light bulb.